Recontextualizing the Teachings ofthe Gita to Higher Education in theCOVID-19 Pandemic Context (Comparative & International Education Series, 2022)
This chapter intends to recontextualize the teachings of the Gita to higher education in the COVID-19 pandemic context and justifies how these teachings can be employed as the guidelines to mitigate the challenges of higher education in the pandemic. This study, as such, is guided by hermeneutics as a method under interpretive design. So the data have been taken from the text, the Gita, and these data have been recontextualized and interpreted in the context of higher education in the COVID-19 pandemic. How to cite in APA:Kamali, H. C. (2022). Recontextualizing the teachings of the Gita to higher education in the COVID-19 context. In E. J. Valeau, R. L. Raby, & U. Gaulee (eds), Shaping a humane world through global higher education: Pre-challenges and post-opportunities during a pandemic (pp. 35-46). STAR Scholars.